Blended Learning Berwawasan Literasi Digital Suatu Upaya Meningkatkan Kualitas Pembelajaran dan Membangun Generasi Emas 2045 - Siti Masitoh (International Consortium of Education and Culture Research Studies, 2018)
The results of the advancement of technology and Informatics has opened up the opportunity of world citizens that belong to Indonesia to take advantage of electronics products, including mobile phones. The results of field observations in the last three years found that the phenomenon of school age children start kindergarten until students are likely to be able to operate the mobile phone. Observe the type of basic literacy, developed by Kemendikbud, every type of basic literacy had the same position with the other basic literacy to be developed, including the type of digital literacy. The six types of basic literacy was developed in an attempt to take Indonesia citizens (especially primary and JUNIOR HIGH SCHOOL students) have the skills the 21st century human being who has the ability to think kiris, krearif, communicative and collaborative as well as character. Phenomena in the field of digital literacy and that mobile phones that can be as a medium of instruction has not been developed in States that made possible can contribute to improve the quality of learning in a Blended Learning settings. Digital literacy for this long purely known in social media can deliver a variety of information related to the things that are needed by the citizens of the community, but still not optimized for the synergistic support increasing the quality of learning.